(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2023)
The current study seek to determine the role of Six Sigma methodology in promoting the implementation of additive manufacturing technology (an exploratory study in the Canadian factory, one of the formations of the General Company for Communications and Power), and based on a basic problem that (Does Six Sigma contribute to enhancing the implementation of additive manufacturing technology?) with the aim of forming a modern industrial environment that is able to produce products that meet the needs of the market in terms of their quality and cost, as well as their suitability to the customer’s requirements that change continuously. Then the data was analyzed and the hypotheses of the study were tested using the statistical software package (SPSS V26), and thus the study reached a set of conclusions, the most important of which is that the additive manufacturing technology is the future technology through which resources can be invested and the environment is preserved from pollution, and the Six Sigma methodology has a positive impact on The performance of organizations by adopting it as a main base in formulating effective strategies for the organization, as well as securing sources of obtaining funding Ward available at the lowest possible cost and highest quality target.